PRIOR OPINION DAN PERTUMBUHAN PERUSAHAAN SEBAGAI PEMODERASI PENGARUH MODEL PREDIKSI KEBANGKRUTAN ALTMAN PADA PEMBERIAN OPINI GOING CONCERN - Dewi, Ni Nyoman Kristiana; Badera, I Dewa Nyoman; Astika, Ida Bagus Putra (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aimed to get empirical proof of prior opinion and company’s growth in moderating the effect of bankruptcy prediction model on going concern opinion. Several previous studies have shown inconsistent results related to the effect of bankruptcy prediction model on going concern opinion. The differences in the results of these study can be completed through a contingency approach and prior opinion and company’s growth expected moderating variable in the relationship between bankruptcy prediction model on going concern opinion. This study uses secondary data. Population in this study are manufacturing companies listed in Indonesia Stock Exchange 2007-2014. The sample in this study is 126 samples were selected by purposive sampling technique. The analysis technique used is logistic regression analysis. The results showed that prior opinion is able to weaken the effect of bankruptcy prediction model on going concern opinion, but the company’s growth is not able to moderate the effect of bankruptcy prediction model on going concern opinion. .
Keywords: going concern opinion, bankruptcy prediction model, prior opinion, company’s growth